2018
DOI: 10.3390/ijms19041199
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Potential Regulators of Glutathione Peroxidases Expression and Their Role in Obesity and Related Pathologies

Abstract: Glutathione peroxidases (GPxs) belong to the eight-member family of phylogenetically related enzymes with different cellular localization, but distinct antioxidant function. Several GPxs are important selenoproteins. Dysregulated GPx expression is connected with severe pathologies, including obesity and diabetes. We performed a comprehensive bioinformatic analysis using the programs miRDB, miRanda, TargetScan, and Diana in the search for hypothetical microRNAs targeting 3′untranslated regions (3´UTR) of GPxs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 160 publications
1
28
0
2
Order By: Relevance
“…In many European countries populations, Se levels are below or borderline the level for optimal Glutathione Peroxidase and Obesity and elderly as independent risk factor of severe COVID-19 (80) Obese hosts exhibit delayed and blunted antiviral responses to influenza virus infection In both Pr, Th for complications: cardiovascular, endotheliitis, thrombosis, and to mitigate cytokine storm (87) In Bioinformatic study, Se deficiency alters miRNAs (miR-185-5p) that regulate selenoproteins expression (GPx) in oxidative stress and obesity (88,89) Obesity is tied to reduction of GPx3 activity in adipose tissue In elderly, Se Pr as in asymptomatic and Th as soon as possible In animal study, Selenite treatment increases GPx3 activity in obese mice (96) Serum Se level is significantly reduced among morbidly obese (106) ex vivo study, Oxidative stress is highly increased in senescent fibroblasts that consume more Se. The addition of Se in these cells, increases GPx activity and decreases ROS (107,110,112) In clinical study, In elderly subjects, the more Se deficiency the higher the mortality rate…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many European countries populations, Se levels are below or borderline the level for optimal Glutathione Peroxidase and Obesity and elderly as independent risk factor of severe COVID-19 (80) Obese hosts exhibit delayed and blunted antiviral responses to influenza virus infection In both Pr, Th for complications: cardiovascular, endotheliitis, thrombosis, and to mitigate cytokine storm (87) In Bioinformatic study, Se deficiency alters miRNAs (miR-185-5p) that regulate selenoproteins expression (GPx) in oxidative stress and obesity (88,89) Obesity is tied to reduction of GPx3 activity in adipose tissue In elderly, Se Pr as in asymptomatic and Th as soon as possible In animal study, Selenite treatment increases GPx3 activity in obese mice (96) Serum Se level is significantly reduced among morbidly obese (106) ex vivo study, Oxidative stress is highly increased in senescent fibroblasts that consume more Se. The addition of Se in these cells, increases GPx activity and decreases ROS (107,110,112) In clinical study, In elderly subjects, the more Se deficiency the higher the mortality rate…”
Section: Discussionmentioning
confidence: 99%
“…Of note, Se attenuates pro-inflammatory gene expression in macrophages (86). miR-185-5p, a Se sensitive microRNA, was identified to regulate six of eight Glutathione Peroxidase and to control the feedback expression of selenoproteins in obese patients (87). Similarly, obesity is also associated with a reduction of Glutathione Peroxidase 3(GPx3) activity in adipose tissue (88).…”
Section: Potential Relationship Between Covid-19 Outcome and Host Selmentioning
confidence: 99%
“…Studies have shown that miR-7 is involved in growth and development, as well as in diseases (Li et al, 2018b;Matoušková et al, 2018;Zeng et al, 2018). However, the way in which miR-7 regulates the proliferation and differentiation of chicken myoblasts remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the silencing of miR-185 increased glutathione peroxidase 2 and selenophosphate synthetase 2 [ 107 ]. In a recent study, several miRNAs were predicted as putative regulators of various glutathione peroxidases [ 108 ].…”
Section: Selenium Regulation Of Micrornas and Long Non-coding Rnasmentioning
confidence: 99%